Pembatasan Usia oleh Perusahaan dalam Rekrutmen Kerja Ditinjau dari Persepektif Hak Asasi Manusia - Rafshahdy Azari Soediro (AHKAM, 2026)
Age-based restrictions in recruitment remain commonly applied by companies in Indonesia, which often specify particular age requirements in job vacancy advertisements on the grounds of efficiency, productivity, and alignment with organizational needs. However, this practice raises serious concerns from a human rights perspective, particularly in relation to the principles of non-discrimination and the right to decent work. This study aimed to analyze age restrictions in recruitment from a human rights standpoint, examine the national and international legal bases governing the right to work, and assess whether age-based limitations can be legally justified. The research employed a normative juridical method with statutory, conceptual, and comparative approaches. The findings indicate that age-based restrictions in recruitment are, in principle, potentially in violation of human rights standards when they are not grounded in objective, rational, and proportionate reasons. The state has an obligation to protect, respect, and fulfill citizens’ rights to work without discrimination, including discrimination based on age. Therefore, more stringent regulations and effective monitoring mechanisms are required to ensure that recruitment practices are consistent with human rights principles and social justice.